2020
DOI: 10.2174/1574884714666190905162237
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and Oxidative Impacts of Short and Long-term Administration of HAART on HIV Patients

Abstract: Background and Objective: There may be possible association among use of HAART, oxidative stress and mitochondrial functions in HIV patients. We evaluated the mitochondrial and oxidative impacts of short and long-term administration of HAART on HIV patients attending the Enugu State University Teaching (ESUT) Hospital, Parklane, Enugu, Nigeria following short and long-term therapy. Methods: 96 patients categorized into four groups of 24 individuals were recruited for the study. Group 1 comprised age-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Malondiadehyde (MDA) is an enzymatic indicator that shows the presence of high-level production of free radicals in the body leading to oxidative stress. The significantly increased level of MDA in HIV positive patients as observed in this study is in keeping with the generally high levels of MDA found in some studies including that of Ikekpeazu et al [9]. This increase was observed with decrease in the levels of antioxidant (SOD and GSH) which is indicative of oxidative stress and lipid peroxidation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Malondiadehyde (MDA) is an enzymatic indicator that shows the presence of high-level production of free radicals in the body leading to oxidative stress. The significantly increased level of MDA in HIV positive patients as observed in this study is in keeping with the generally high levels of MDA found in some studies including that of Ikekpeazu et al [9]. This increase was observed with decrease in the levels of antioxidant (SOD and GSH) which is indicative of oxidative stress and lipid peroxidation.…”
Section: Discussionsupporting
confidence: 91%
“…Highly active antiretroviral therapy (HAART) is presently the therapy of optimal considerations for HIV-infected patients [9]. However, despite the amazing viral replication suppression and immune response restoration, long-term HAART appears of limited use in many patients because of additional adverse effects and/or regimen adherence difficulties [10].…”
Section: Introductionmentioning
confidence: 99%
“…Even though it might be premature to explain the exact mechanism responsible for the higher levels of GSH observed in the treatment groups, in contrast to the high MDA levels, it may possibly be as a result of the release of GSH into the extracellular microenvironment by astrocytes which then generates precursors for neuronal GSH synthesis (Hirrlinger et al 2002). Results from the present study showed that the lamivudine and tenofovir might adversely alter the histoarchitectural integrity of the prefrontal cortex, possibly due to increased mitochondrial damage, which is a source of free radicals (Ikekpeazu et al 2020). It should be noted that the NNRTIs have also been implicated in the oxidative stress hypothesis.…”
Section: Discussionmentioning
confidence: 63%
“…This study did not find significant difference in the cf-mtDNA concentration of ART treated HIV+ patients compared with healthy controls, even when they were matched to their respective age groups. Some of the previous studies reported significant difference of mtDNA concentration between healthy individuals and ART-treated HIV infected patients or ART-prophylactic treated children [36]- [39] and [35] also reported a significant depletion of mtDNA copy number among ART treated HIV patients compared to healthy controls in Enugu, a South-eastern part of Nigeria. However, [32] did not find marked variation in a study involving a cohort of HIV infected and non-infected children.…”
Section: Discussionmentioning
confidence: 91%